(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Attracting foreign investment is an important component of the economic development of many countries. The main areas in which countries attract foreign investment may differ depending on their economic needs, priorities and competitive advantages.